Using Metacognitive Learning Strategy to Improve Reading Comprehension - Afdaleni Afdaleni (Universitas Negeri Padang, 2014)
The learners’ success in their reading comprehension depends on many factors. The learner is one the important factors that can determine his/her success in reading comprehension. The learners may do many things and activate themselves in order that they may improve their reading comprehension; it is learning strategy. Metacognitive Learning Strategy is one of the indirect learning strategy that may influence the students in their success in their learning. Metacognitive strategies help learners to regulate their learning including planning, self-monitoring and self-evaluation. Then, metacognitive strategy sets consist of centering your learning; helps learners to converge their attention and energies on language skills, activities, skills, or materials, arranging and planning your learning; help learners to organize and plan so as to get the most out of language learning, evaluating your learning; aiding learners in checking their language performance. Since learners have an important role in his/ her success in reading comprehension, it is considered that they should aware the metacognitive learning strategy itself in order that they may apply them in their reading comprehension activity. The paper is about metacognitive learning strategy to improve Reading Comprehension. It is expected that this article can become useful information for the teachers, learners and readers who concern with the reading comprehension in general.